2019
DOI: 10.1111/jfpp.14213
|View full text |Cite
|
Sign up to set email alerts
|

Application of supplemental UV‐B radiation in pre‐harvest to enhance health‐promoting compounds accumulation in green and red lettuce

Abstract: The plants (green and red lettuce) were exposed to daily doses of UV‐B radiation for 1 hr for two weeks during growth. UV‐B‐treated green lettuces at the second week presented a greater content of quercetin than the control plants. Caffeoyltartaric acid, caffeoylquinic acid and caffeoylmalic acid also showed a significant accumulation in green lettuce after two weeks of UV‐B treatment in comparison to those non‐treated. Regarding carotenoid content, lutein, neoxanthin, and V + A + Z showed significant increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
5
10
0
Order By: Relevance
“…However, many manuscripts have investigated UV-B-induced effects in several crops, mostly agreeing on the general positive impact of UV-B irradiation on the total phenolic content [16]. In accordance with our results, a pre-harvest UV-B supplementation increased the total phenolic and flavonoid concentration in basil [70,71] and lettuce [72]. UV-B was also effective in enhancing phenolic and flavonoid content, depending on the UV-B dose applied, when exposing plants soon after germination, as observed in rice and wheat seedlings [73,74], and in mung bean and broccoli sprouts [17,18].…”
Section: Uv-b Treatment Negatively Impacts the Productivity And The P...supporting
confidence: 90%
“…However, many manuscripts have investigated UV-B-induced effects in several crops, mostly agreeing on the general positive impact of UV-B irradiation on the total phenolic content [16]. In accordance with our results, a pre-harvest UV-B supplementation increased the total phenolic and flavonoid concentration in basil [70,71] and lettuce [72]. UV-B was also effective in enhancing phenolic and flavonoid content, depending on the UV-B dose applied, when exposing plants soon after germination, as observed in rice and wheat seedlings [73,74], and in mung bean and broccoli sprouts [17,18].…”
Section: Uv-b Treatment Negatively Impacts the Productivity And The P...supporting
confidence: 90%
“…Thus, the UV-shielding flavonoids are mainly found in the plant epidermis and act as UV protectants – a plant’s sunscreen. Studies have reported that flavonoid contents increase in lettuce grown with additional UVA, UVB and UVC light ( Lee et al., 2014 ; Assumpção et al., 2019 ).Using covered systems for crop cultivation, changes in UV light occur due to the reduced transmittance of the materials used. Indeed, UVA and UVB light are reduced by using polytunnels in this study, resulting in lower total and individual flavonoids than seen in cultivation without polytunnels.…”
Section: Discussionmentioning
confidence: 99%
“…The content of the anthocyanin cyanidin-3-malonylglucoside, present only in red lettuce, also accumulated at higher levels after both one and two weeks of UV-B treatment. However, caffeoylmalic acid was negatively affected by both UV-B doses [ 209 ].…”
Section: Uv-b Radiationmentioning
confidence: 99%